OPTICAL TAMM STATES AT INTERFACES OF DIFFERENT PERIODIC MEDIA CONTAINING SINGLE AND DOUBLE NEGATIVE MATERIAL LAYERS - Saeed, Maryam; Ali, Munnaza Z. (The Nucleus, 2013)
Optical Tamm States (OTS) are investigated at the interfaces of semi-infinite metal and finite one dimensional periodic structures. Three types of periodic structures are considered here. Initially a one dimensional structure of alternate regular material layers is considered. The other two structures consist of alternate left-handed material and regular material layers and alternate single negative layers. The transfer matrix approach is used to derive the dispersion relation for the TE mode Optical Tamm States (OTS). The dispersion relations is plotted in the photonic band gap frequency range and analyzed by changing the structure parameters.